THU0328 The Role of Salivary Gland Ultrasound in Sjogren Syndrome: A Single Center Experience. (23rd January 2014) - Germanò, G.; Possemato, N.; Addimanda, O.; Caruso, A.; Dardani, L.; Macchioni, P.; Salvarani, C.
Abstract : Background: There is increasingly scientific evidence of salivary gland ultrasonography accuracy and usefulness in diagnosing Sjogren Syndrome. [2 -3 ] Objectives: To assess the role of salivary gland ultrasound in the diagnostic process of Sjogren Syndrome. Methods: 82 patients with suspected Sjogren Syndrome from a single center were evaluated. Demographic (age and sex), clinical (sicca syndrome, artralgia), ultrasonographic (salivary gland ultrasound following the score proposed by Ariji et al) [4 ], serologic (anti nuclear antibodies – ANA, anti ENA, anti HCV) and histological (salivary glands biopsy with Chisholm-Mason score evaluation) features were analyzed. Patients were classified according to ACR/EULAR criteria for SS (AEC).[1 ] Results: All patients with HCV infection were counted out as well as all the patients with one of the exclusion criteria present in the Primary Sjogren Syndrome classification. Male/female ratio was 1/9; 91.2 % of patients presented xerostomia, 75% xerophthalmia. Schirmer test was positive in 72% of the patients; break up time positive in 65%. The biopsy was positive (Chisholm and Mason score ≥1) in 61% and ultrasound was positive (score ≥2 out of 4) in 40.2%. ENA test (SSA and\or SSB) was positive in 37.4%. The diagnosis of Sjogren Syndrome has been assessed, according to AECG classification criteria, in 36 patients out of 82 (43.9%). 80.6% of patients with positive ultrasound were classified as affected by Sjogren Syndrome, 89.1% of patients with negative ultrasound didn't fill the classification criteria. The ultrasound score presented a positive likelihood ratio of 4.58 (95% confidence interval 2.34 8.98) and a negative one of 0.135 (0.058<x<0.313). The test showed a sensibility of 80.6% and a specificity of 89.1%. Concordance (Cohen K) between classification criteria and US score was 0.701 (medium level), higher than that between classification criteria and biopsy Chisholm-Mason score (0.572). Surprisingly ENA screening didn't add diagnostic power to the ultrasound scan due to a wide overlapping of the two tests. Conclusions: In our experience salivary gland ultrasound seems to be an useful tool in the diagnostic process of Sjogren Syndrome due to its good sensibility and specificity. Moreover the exam is simple to perform, fast, incruent and well accepted by patients. References: Vitali C, Bombardieri S, Jonsson R, et al. Classifi cation criteria for Sjögren's syndrome: a revised version of the European criteria proposed by the American-European Consensus Group. Ann Rheum Dis 2002;61:554–8. Cornec D et al. Contribution of salivary gland ultrasonography to the diagnosis of Sjögren's syndrome: Toward new diagnostic criteria? Arthritis Rheum. 2013 Jan;65(1):216-25. Milic V. et al. Ultrasonography of major salivary glands could be an alternative tool to sialoscintigraphy in the American-European classification criteria for primary Sjogren's syndrome. Rheumatology (Oxford). 2012 Jun;51(6):1081-5 Ariji Y, Ohki M, Eguchi K, et al. Texture analysis of sonographic features of the parotid gland in Sjögren's syndrome. AJR Am J Roentgenol 1996;166:935–41. Disclosure of Interest: None Declared